Assédio moral como fenômeno do mundo contemporâneo do trabalho: revisão da produção brasileira nos últimos cinco anos - Oliveira, Laura Gomes de (2018)
The main objective of this study is to analyze the relationship between the phenomenon of moral harassment and the characteristics of the world of contemporary work. In addition, realize the changes that have occurred in the world of work throughout history and characterize bullying as the fruit of this context. The methodology used was a systematic literature review, which, consists of a synthesis of studies containing clear objectives, methods and methodology that can make it reproducible. It is a form of research that makes use of the results of the studies of other researchers as a way to theoretically base a theme. The database used was Scielo Brazil and CAPES and, by adopting the inclusion and exclusion criteria, 39 articles were selected for analysis, including theoretical and empirical articles. In the results of the found articles one can define four main categories: Violence in Work / Social Violence; Organizational Factors that Propitiate Moral Harassment / Management Policies; Context of the work relations in the contemporaneity and Characteristics of Moral Harassment. Thus, it was concluded in the analysis by means of the selected categories that Moral Harassment is done as psychological violence that is closely related to labor relations based on the capitalist economic model, since it is reaffirmed by the valorization of hierarchical powers, stimulate competitiveness in the game of inclusion of a few and exclusion of many, and by fostering this context, breaks with the bonds of class solidarity making individuals more exposed to harassment as behavior and institutional policy.